Meta-analysis on atmospheric carbon capture in Spain through the use of conservation agriculture - González-Sánchez, E.J.; Ordóñez-Fernández, R.; Carbonell-Bojollo, R.; Veroz-González, O.; Gil-Ribes, J.A. (Soil & tillage research, 2012)
► The manuscript analyses over a decade research papers of 11 groups focused on the study of soil as carbon sink. ► Conservation agriculture practices were studied both in arable and in woody crops in comparison to conventional tillage. ► No tillage and cover crops in orchards show the best results as carbon sink. ► Minimum tillage may be over emitting CO2 in comparison to conventional tillage in Spain. ► Crop rotations increases C sequestration when compared to monocultures in arable crops and so do native cover crops in woody crops. Conservation agriculture (CA) helps to mitigate climate change. Firstly, the modifications introduced by CA on the carbon dynamics in the soil directly result in an increase of the carbon (C) in the soil fraction. Secondly, CA drastically reduces C oxidation processes by diminishing the mechanical manipulation of the soil. Spain's position in relation to the Kyoto Protocol must be improved, as is one of the European countries in a non-compliance situation. With the aim of providing knowledge about the potential of CA as C sink in Spain, 29 articles on this subject were reviewed. According to 2010 CA uptake, the results demonstrated that conservation practices have the potential to promote the fixation in soil of about 2Ggyear−1 more C than traditional tillage (TT) systems. As indicated by Tebrügge (2001), 3.7Mg of CO2 are generated from 1Mg of C through microbial oxidation processes taking place in the ground, meaning that through CA almost 7.5Gg of CO2 could be sequestered from the atmosphere every year until the equilibrium is reached. C fixation was found to be irregular over time. C fixation rates were high in newly implemented systems during the first 10years, reaching top values of 0.85Mgha−1year−1 for no-tillage (NT) and 1.54Mgha−1year−1 for cover crops (CC) implemented in-between perennial tree rows. After those first 10years, it followed a period of lower but steady growth until equilibrium was reached. Nevertheless, C decreases of 0.16Mgha−1year−1 in the first 10years may be expected when practicing minimum tillage (MT). C sequestration rate resulted higher in case farmers do crop rotations in NT and MT rather than monoculture. In woody crops, studies reported higher C fixation values for native species when compared to sowed CC. Also, climate conditions seem to affect C sequestration rate in Spain. Although in NT differences observed between maritime and continental climates are not pronounced, as approximately 25% of the values recorded in both climates are equal, in the case of MT about 75% of maritime climate values result higher than the continental situation.